METHOD FOR MEASURING DISTORTION IN WIDE-ANGLE VIDEO CHANNELS - Krotov, Aleksander; Volkov, Dmitry; Romanov, Nikolay; Gryaznov, Nikolay; Sosnov, Evgeny; Goryachkin, Dmitry (Journal of Applied Engineering Science, 2018)
Methods for correcting aberrations of images, obtained by an optoelectronic camera with the use of calibration function measured preliminary, gain wide acceptance in recent years.  For the most part these methods are not characterized by high accuracy and are typically used for cameras with objectives having rather high relative distortion. In this article the method is discussed for measuring distortion of a wide-angle objective for calibration of photoelectronic cameras designed to measure angular coordinates of remote objects with the accuracy as high as 10 arcsec. It is proposed to use an air-mirror wedge as a test object, which allows creating a sheaf of collimated beams. The calibration function of the photoelectric camera is calculated by mathematical post-processing of the captured frames. The proposed method has undergone experimental approbation for photoelectronic cameras with a full angular field of view of 21 degree and an angular pixel size of 20 arcsec. The subpixel accuracy of determining the calibration function is demonstrated.